Ramadhan Themes in Islamic Education Using Upin and Ipin Media - Ariyanto, Fiqi; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Audio-visual media are crucial in education, enhancing students' understanding and retention. Specific Background: In Islamic Religious Education (IRE), particularly during the Ramadhan fasting theme, effective use of audio-visual media can engage students actively. However, there is a gap in knowledge regarding their application in elementary schools. Aims: This study examines how teachers at Jagul State Elementary School utilize audio-visual media, specifically the animated series